Cork oak woodlands patchiness: A signature of imminent deforestation? - Costa, Augusta; Madeira, Manuel; Plieninger, Tobias (Applied Geography, 2014)
The cork oak (Quercus suber L.) woodlands of the agroforestry landscapes of Southwestern Iberia are undergoing drastic change due to severe natural and anthropogenic disturbances. These may eventually result in woodland loss or deforestation, the final step of an ongoing process of woodland degradation. Monitoring changes in the spatial patterns of woodlands – especially fractional canopy cover of woodlands and/or their patchiness in the landscape mosaic – potentially enables forecasting of loss and responding to it at an early stage. We examine the degradation process in two cork oak woodlands, resulting from distinct disturbances, wildfire and oak mortality, aimed at evaluating the changes, trends and deviations of the spatial attributes of these woodlands as they move from an initial (less disturbed ecosystem) to a final state (more disturbed ecosystem). While undergoing disturbances, both woodlands exhibited similar trends of decreasing fractional canopy cover and decreasing number of larger patches. Patchiness rather than fractional canopy cover seems, however, to be potentially more useful as a signature of imminent oak woodlands deforestation, given that its contrast before and after disturbance was much higher. The structural dynamics of oak woodlands is a crucial but neglected issue that needs greater attention from policy forums working toward their conservation and restoration as well as from stakeholders and society as a whole.
Keywords: Forest degradation; Fractional canopy cover; mediterranean landscape; Patch size–frequency distribution; Power-law function; Quercus suber L.

How resilient is Quercus suber L. to cork harvesting? A review and identification of knowledge gaps (Forest Ecology and Management, 2012)
Cork oak (Quercus suber L.) woodlands are ecologically sensitive and human-supported areas which strongly rely on the high market value of cork for their sustainability. Cork harvesting is a forestry practice specific to this Mediterranean evergreen oak, whereby the bark (cork) is periodically removed from stems and branches over the whole tree lifetime. This practice is a strain factor for the tree, particularly because it is performed during the most stressful time of the year, and also because stripped oaks become more vulnerable to pathogens and environmental hazards such as wildfires.This review gathers and analyzes information about tree responses to cork harvesting. Cork removal leads to phellogen destruction and subsequent regeneration. Upon each harvesting, the tree faces important losses of water, released from the suddenly exposed living cells, and of cork. Immediate responses relate to stem healing mechanisms, leaf stomatal closure and prompt production of new cork layers by the restored phellogen, the latter actually representing the most evident response of Q. suber to cork harvesting. Further strategies to compensate for water and cork losses are insufficiently understood, but possibly include prolonged reduction of leaf transpiration (and consequent reduction of photoassimilation), increased water uptake from the soil, use of reserves and changes in whole-tree energy allocation to support cork regeneration. Cork stripping by unskilled workers may leave wounds on the tree, which eventually hinder cork regeneration and lead to premature tree death. The relationship between current cork harvesting practices (e.g. harvesting intensities or periodicity) and tree resilience is not quite established. Higher stripping pressures seem to trigger more pronounced or drastic tree responses and/or to enhance their decline. A major conclusion is that the available information is still too scarce to allow for a consistent evaluation of the effects of cork harvesting on cork oak and on its associated woodlands. So far, few studies have addressed how tree resilience relates to harvesting intensities, a crucial issue to enable improved tree and stand management strategies and to ensure adequate conservation of these sensitive forest systems.

How resilient is Quercus suber L. to cork harvesting? A review and identification of knowledge gaps (Forest Ecology and Management, 2012)
Cork oak (Quercus suber L.) woodlands are ecologically sensitive and human-supported areas which strongly rely on the high market value of cork for their sustainability. Cork harvesting is a forestry practice speciﬁc to this Mediterranean evergreen oak, whereby the bark (cork) is periodically removed from stems and branches over the whole tree lifetime. This practice is a strain factor for the tree, particularly because it is performed during the most stressful time of the year, and also because stripped oaks become more vulnerable to pathogens and environmental hazards such as wildﬁres. This review gathers and analyzes information about tree responses to cork harvesting. Cork removal leads to phellogen destruction and subsequent regeneration. Upon each harvesting, the tree faces important losses of water, released from the suddenly exposed living cells, and of cork. Immediate responses relate to stem healing mechanisms, leaf stomatal closure and prompt production of new cork layers by the restored phellogen, the latter actually representing the most evident response of Q. suber to cork harvesting. Further strategies to compensate for water and cork losses are insufﬁciently understood, but possibly include prolonged reduction of leaf transpiration (and consequent reduction of photoassimilation), increased water uptake from the soil, use of reserves and changes in whole-tree energy allocation to support cork regeneration. Cork stripping by unskilled workers may leave wounds on the tree, which eventually hinder cork regeneration and lead to premature tree death. The relationship between current cork harvesting practices (e.g. harvesting intensities or periodicity) and tree resilience is not quite established. Higher stripping pressures seem to trigger more pronounced or drastic tree responses and/or to enhance their decline. A major conclusion is that the available information is still too scarce to allow for a consistent evaluation of the effects of cork harvesting on cork oak and on its associated woodlands. So far, few studies have addressed how tree resilience relates to harvesting intensities, a crucial issue to enable improved tree and stand management strategies and to ensure adequate conservation of these sensitive forest systems.

Analysis of spatial patterns of oak decline in cork oak woodlands in Mediterranean conditions - Costa, Augusta; Pereira, Helena; Madeira, Manuel (Annals of Forest Science, 2010)
• Cork oak mortality is a recurrent problem in southwestern Portugal. Despite the perception of increasingly visible damage in oak woodlands on drought-prone sites, the role of the various environmental factors in their decline is not clear. • To describe the spatial patterns of cork oak (Quercus suber L.) mortality, a cork oak mortality index (MI) was determined for each landscape feature (agroforestry system, soil type, slope and aspect) using a GIS approach. To achieve this goal, a logistic regression model was formulated analyzing interactions between landscape attributes and allowing a prediction of cork oak mortality. • Maximum values of MI were found in (i) shrublands and open woodlands with shrub encroachment (MI 6 and 3, respectively), where competition for soil water between tree and understory increases; and (ii) on lower slopes in the rounded hilltops and smooth hillsides or shallow soils where access to groundwater resources during summer drought is diﬃcult. • The model highlighted the importance of the agroforestry systems on cork oak mortality and may be used to identify sensitive areas where mitigation actions should be employed in a scenario of increasing drought severity in these Mediterranean ecosystems.
Keywords: Logistic regression; Oak decline; oak mortality; Quercus suber L.; Remote sensing

Análise Espacial da Mortalidade do Sobreiro em S. Bartolomeu da Serra (Santiago do Cacém) (Congresso Florestal Nacional, 6º, Ponta Delgada, 2009 - A floresta num mundo globalizado, 2009)
Avaliou-se a distribuição espacial da mortalidade do sobreiro (Quercus suber L.) na área da freguesia de S. Bartolomeu da Serra (Santiago do Cacém), integrada numa região em que ela ocorre com elevada incidência, através de técnicas de detecção remota (SIG), e determinou-se a probabilidade de ocorrência de mortalidade através da aplicação de um modelo de regressão logística. Determinou-se um índice de mortalidade e identificaram-se as unidades fisiográficas com maior probabilidade de mortalidade em três sistemas agroflorestais distintos: floresta de sobreiro (florestas densas), montado de sobro tradicional (florestas abertas em sistemas dominantemente agrícolas, com culturas arvenses sob coberto) e incultos (florestas abertas em sistemas dominantemente incultos, com matos sob coberto). A mortalidade do sobreiro é significativamente diferente para os três tipos de sistemas agro-florestais. A mortalidade é influenciada por características físicas da paisagem como o solo, o declive e a exposição. Em solos pouco profundos ou em solos mais compactos, a mortalidade é mais frequente, mostrando a importância do desenvolvimento radicular em profundidade do sobreiro em regiões susceptíveis a extensos períodos de secura.

Análise Espacial da Mortalidade do Sobreiro em S. Bartolomeu da Serra (Santiago do Cacém) - Costa, Augusta; Pereira, Helena; Madeira, Manuel (Congresso Florestal Nacional, 6º, Ponta Delgada, 2009 - A floresta num mundo globalizado, 2009)
Avaliou-se a distribuição espacial da mortalidade do sobreiro (Quercus suber L.) na área da freguesia de S. Bartolomeu da Serra (Santiago do Cacém), integrada numa região em que ela ocorre com elevada incidência, através de técnicas de detecção remota (SIG), e determinou-se a probabilidade de ocorrência de mortalidade através da aplicação de um modelo de regressão logística. Determinou-se um índice de mortalidade e identificaram-se as unidades fisiográficas com maior probabilidade de mortalidade em três sistemas agroflorestais distintos: floresta de sobreiro (florestas densas), montado de sobro tradicional (florestas abertas em sistemas dominantemente agrícolas, com culturas arvenses sob coberto) e incultos (florestas abertas em sistemas dominantemente incultos, com matos sob coberto). A mortalidade do sobreiro é significativamente diferente para os três tipos de sistemas agro-florestais. A mortalidade é influenciada por características físicas da paisagem como o solo, o declive e a exposição. Em solos pouco profundos ou em solos mais compactos, a mortalidade é mais frequente, mostrando a importância do desenvolvimento radicular em profundidade do sobreiro em regiões susceptíveis a extensos períodos de secura.
The following values have no corresponding Zotero field: periodical: Congresso Florestal Nacional, 6º, Ponta Delgada, 2009 - A floresta num mundo globalizado
Keywords: declínio do montado de sobro; detecção remota; mortalidade do sobreiro; Quercus suber L.; regressão logística